Antibacterial Activity of Myrmecodia pendens (Ant Nest Plant) against Multidrug Resistance Bacteria from Clinical Samples - Prastiyanto, Muhammad Evy; Ernanto, Aditya Rahman; Darmawati, Sri; Maharani, Endang Tri Wahyuni; Mulyanto, Arif; Rukmana, Rizal Maarif; Putri, Wahyu Aristyaning; Kusmita, Lia; Sah, Shiv Kumar; Geleta, Daniel (Majalah Obat Tradisional, 2026)
The emergence of multidrug-resistant (MDR) bacteria causes a substantial barrier to treatment, demanding the development of new antibacterial medicines. Myrmecodia pendens (ant nest plant), an indigenous medicinal species, is esteemed for its potential medicinal properties. This study aimed to examine the antibacterial efficacy of M. pendens extracts against MDR bacterial strains (Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Citrobacter freundii, and Pseudomonas aeruginosa) obtained from clinical samples. Extracts were prepared via maceration using ethanol, chloroform, and n-hexane solvents. Antibacterial efficacy was evaluated using the agar diffusion method, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) assays. The ethanol solvent extract exhibited the most significant antibacterial activity, particularly against P. aeruginosa, with an inhibition zone of 23.15 ± 0.21 mm at 100 mg/mL. The MIC and MBC values were 3.13 mg/mL and 12.5 mg/mL, respectively. The chloroform and n-hexane extracts showed lower, but comparable, inhibitory effects against the tested strains. These findings provide compelling evidence that M. pendens extracts, especially the ethanol extracts, represent a promising source for developing alternative antibacterial agents to combat MDR infections.